P521 Increases in the estimated number of reported gonorrhea cases among men who have sex with men (MSM): the role of testing. (14th July 2019) - Williams, Austin; Weston, Emily; Gift, Thomas; Torrone, Elizabeth
Abstract : Background: Interpreting trends in rates of reported cases of gonorrhea is difficult because infections, particularly extra-genital infections, are often asymptomatic and increased screening coverage will result in increased case detection. In the absence of national data on screening coverage among men who have sex with men (MSM), we estimated trends in MSM testing in the United States given a range of positivity estimates. Methods: We estimated the number of tests that would have had to occur to identify the estimated number of reported gonorrhea cases among MSM in a given year. The number of tests was calculated by dividing the annual number of estimated cases among MSM (based on sentinel surveillance) by estimated test positivity among MSM (based on published literature). We calculated the estimated number of tests under both low positivity (3.5%) and high positivity (10%), as well as the effect of stable and changing positivity during 2016–2017. Results: The estimated number of reported gonorrhea cases among MSM increased by 17.9% during 2016–2017 (from 163, 537 to 192, 740). We estimated that 1.9 million (assuming 10% positivity) to 5.5 million (assuming 3.5% positivity) tests performed among MSM would be needed to detect the estimated number of gonorrhea cases among MSM in 2017. This represents an increase of approximately 290, 000 to 830, 000 tests over the estimated number of tests conducted in 2016. Alternatively, if the number of tests was stable over time, a 0.6 to 1.8 percentage point increase in positivity from 2016 to 2017 would be consistent with the increase in observed cases. Conclusion: We provide a framework to inform trends in case rates by analyzing the impact of changes in positivity and testing over time. Our analysis implies that estimated increases in reported gonorrhea cases among MSM likely resulted from both increased screening and increased incidence. Disclosure: No significant relationships.